Preserving the Authenticity of Qirā’āt Sab'ah: A Comparative Study of Musyāfahah Methods at Al-Hasan and Al-Munawwir Boarding School - Roni Susanto; Ahmad Munir; Basuki Basuki (Ushuluddin, Adab, and Dakwah Faculty of State Islamic University Ponorogo, 2025)
This study examines the challenges in maintaining the authenticity of qirā’āt sab’ah in the face of technological advances, focusing on the credibility of the sanad and the originality of the readings. Using qualitative methods, this study compares the application of the musyāfahah method in Al-Hasan Tahfīz Quran Islamic Boarding School, Ponorogo, and Al-Munawwir Tahfīz Quran Islamic Boarding School, Krapyak, Yogyakarta, through interviews with informants, observation, and documentation. The findings of this study revealed three important things: (1) both Boarding Schools have the same qirā’āt sab’ah sanad lineage, which is supported by a syahādah (certificate); (2) Al-Munawwir Boarding School emphasizes credibility and originality through strict standardization, while Al-Hasan Boarding School adopts a more practical and inclusive approach; and (3) the transformation of Al-Hasan Boarding School promotes broader participation, increasing the number of students, while Al-Munawwir Boarding School focuses on cognitive depth through classical musyāfahah phases. REFERENCES Abidin, Nurul Huda Zainal, Najmiah Omar, and Nor Hafizi Yusof. “Concepts and Implementation of Talaqqi And Musyafahah Methods in Learning the Quran.” Malaysian Journal For Islamic Studies 3, no. 1 (2019): 27–35. https://journal.unisza.edu.my/mjis/index.php/mjis/article/view/81. ABLAY, Rıfat. “Hadis Mecmualarında Yer Alan Kıraate Dair Hadislerin Değerlendirilmesi ve Bu Hadislerin Kıraat İlmindeki Yeri.” Artuklu Akademi 9, no. 1 (2022): 179–96. https://doi.org/10.34247/artukluakademi.1069435. Abuhamdia, Zakaria Ahmad. “Between Veneration for the Text and Vernacularization of the Spoken Form in Quran Recitation.” Journal of Literature, Languages and Linguistics 18 (2016): 44–49. Ahmad, La Ode Ismail, Muhammad Ali, Mirwan Mirwan, Abdul Rahman Sakka, and Risna Mosiba. “Bullying on Social Media: Primitive Behavior Against Prophetic Marchals From A Hadith Ahkam Perspective.” Samarah 8, no. 1 (2024): 79–104. https://doi.org/10.22373/sjhk.v8i1.20189. Ahmed, Dr. Muneer, Dr. Aijaz Ali Khoso, and Muhammad Hammad. “The Efforts of Ulma for the Ilm e Qiraat, &Tajweed in the Indian Subcontinent.” Al Khadim Research Journal of Islamic Culture and Civilization 3, no. 1 (2022): 92–110. https://doi.org/10.53575/arjicc.v3.01(22)a7.92-110. Allison, M, MPH, Schmidt, Leah M., Ranney, Jessica K., Pepper, and Goldstein, Adam.